Design of Fresh Fruit Bunches Lifter using Truck Weight Energy Based on Hydraulic System - Dionisius Dwi Wicaksono; Adhiasta Faris Setiabudi; Hanifa Farafisha; Dimas Panji Hasmoro; Patricia Yohaneta Gendis Kusmaningjati; Wawan Hermawan (PERTETA, 2023)
The process of lifting fresh fruit bunches (FFB) of oil palm to trucks is generally still done manually, with a heavy workload and potential for injury. The existing lifting equipments are powered by an internal combustion engine at a high cost. The purpose of this study was to design and test an equipment for lifting FFB of oil palm into the bed of a truck by utilizing the weight of the truck. The weight on the rear wheels of the truck when backing is used to press a pair of hydraulic cylinders whose pressure is transferred to a hydraulic cylinder driving a scissor type lifting mechanism. FFB which are loaded in a low trough, can be loaded onto the truck easily and quickly. This lifter was designed to lift 400 kg of FFB with a lifting height of 2.4 m. In the top position, the FFB bed is inclined 20o so that it slides into the tailgate. The test results show that this lifter could perform well with a work capacity of 17.22 tons/hour, 2.3 times greater than the manual capacity, and with low work risk. The basic operational cost is IDR 4,894/ton FFB while manually it is IDR 9,008/ton FFB.